SURVEY SINGKAT MAMALIA DI HUTAN DIPTEROKARPA DATARAN RENDAH, HUTAN LINDUNG BATU BEROK, LONG PAHANGAI, KALIMANTAN TIMUR - Rustam Rustam (Fakultas Kehutanan Universitas Mulawarman, 2017)
ABSTRACTThe aimed of this research is to know of mammals composition in dipterocarpa lowland forest, Batu Berok Protection Forest (BBPF), Long Pahangai, East Kalimantan. Combination method was done in this research, there is camera trapping survey, captured, direct and un-direct inventory by line transects and interview with local people. I have used 10 set of camera trapping, 50 cage traps, and 3.5 km line transect.Total 32 species of mammals were detected in this area, comprising 8 ordo (Scandentia, Dermoptera, Chiroptera, Primates, Pholidota, Rodentia, Carnivora and Artiodactyla) and 19 family (Tupaiidae, Cynocephalidae, Pteropedidae, Tarsiidae, Cercopithecidae, Hylobatidae, Manidae, Sciuridae-Sciurinae, Sciuridae-Petauristinae, Muridae, Hystricidae, Ursidae, Mustilidae, Viverridae, Felidae, Suidae, Tragulidae, Cervidae, and Bovidae) including Sun bear Helarctos malayanus, Sambar deer Rusa unicolor, Banded Palm Civet Hemigalus derbyanus, Clouded Leopard Neofelis diardi, and Tarsius Tarsius bancanus. The composition of mammals illustrates a pyramid pattern in the food chain which mean is very feasible for the habitat of mammals. Genus and Family Index illustrate the diversity of mammal in the study area 54% of mammals’ species in East Kalimantan and 56% of mammals’ species in Borneo. By IUCN redlist, 4 species included as endangered species and 8 species as vulnerable, 16 species included in appendix of CITES and 10 species included in the Indonesian government regulation (PP. 7/1999) as protected species.The diversity of mammal in BBPF by quick survey was relatively hight, but as a protected forest this area was not good managed whereas located in the central of heart of Borneo. Intervention by government program is deeply needed.Key word: camera trapping, cage trap, food chain, IUCN ABSTRAKTujuan penelitian ini adalah untuk mengetahui komposisi mamalia di hutan dipterokarpa dataran rendah, Hutan Lindung Batu Berok (HLBB), Long Pahangai, Kalimantan Timur. Kombinasi metoda telah dilakukan pada penelitian ini, yaitu kamera otomatis, penangkapan, pengamatan langsung dan tidak langsung dengan transek, serta wawancara dengan masyarakat lokal. Digunakan 10 kamera otomatis, 50 perangkap mamalia kecil dan 3.5 km transek.Total 32 species mamalia telah terdeteksi di kawasan ini termasuk ke dalam 8 ordo (Scandentia, Dermoptera, Chiroptera, Primates, Pholidota, Rodentia, Carnivora and Artiodactyla) dan 19 famili (Tupaiidae, Cynocephalidae, Pteropedidae, Tarsiidae, Cercopithecidae, Hylobatidae, Manidae, Sciuridae-Sciurinae, Sciuridae-Petauristinae, Muridae, Hystricidae, Ursidae, Mustilidae, Viverridae, Felidae, Suidae, Tragulidae, Cervidae, and Bovidae), termasuk Beruang Madu (Helarctos malayanus), Rusa (Rusa unicolor), Musang Belang (Hemigalus derbyanus), Macan Dahan (Neofelis diardi), and Krabuku Ingkat (Tarsius bancanus) mamalia yang ditemukan menggambarkan pola piramida dalam rantai makanan, yang berarti bahwa kawasan ini sangat layak untuk habitat mamalia. Indeks genus dan family menggambarkan keragaman mamalia di area studi sebesar 54% dari mamalia yang ada di Kalimantan Timur dan 56% dari mamalia di Kalimantan. Berdasarkan daftar jenis species langka dan hampir punah IUCN, 4 species termasuk species terancam punah, 8 jenis termasuk species rentan, 16 species termasuk dalam lampiran CITES dan 10 species termasuk species yang dilindungi berdasarkan Peraturan Pemerintah No. 7 Tahun 1999.Berdasarkan survey singkat ini keragaman mamalia di HLBB relatif tinggi, tetapi sebagai hutan lindung kawasan ini tidak dikelola dengan baik padahal kawasan ini berada di pusat jantung Kalimantan. Program pemerintah untuk mengelola kawasan ini sangat diperlukan.Kata kunci: kamera otomatis, perangkap mamalia kecil, rantai makanan, IUCN